Średniowieczne uniwersum strachu jako metafora współczesności w parabolicznej opowieści o zniewoleniu przez system (Ciemności kryją ziemię Stanislava Barabáša według Jerzego Andrzejewskiego, 1989) - Kolasińska-Pasterczyk, Iwona (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2025)
Inspired by researchers investigating the relationship between cinema and history, namely, Marc Ferro (noting the possibility that presenting ancient societies allows for a better understanding of contemporary ones) and Dorota Skotarczak (pointing out the importance of visualizing the past), the author proposes a case of a film (of literary provenance) in which a historical “costume” is a mask allowing for a substitute representation of contemporary reality and providing an excuse to universalize the message. Darkness Covers the Earth (Torquemada, dir. Stanislav Barabáš, 1989) is an example of a film in which the dark pages of ancient history (the Spanish Inquisition in the 15th century) function as a prefiguration of the totalitarian systems of the 20th century. It is also a kind of parable set in historical realities, prompting reflection on the essence of history. It exemplifies the path from historical staffage to historiosophy. The historiosophical tone of Barabáš’s film was encoded in three confessional situations.